Cultural and Historical Heritage of the City of Sisak: Strategies for Preservation and Enhancement - Kadoić, Lidija; Dučkić, Magdalena; Drmić, Iva Tara; Barišić, Petra (Strategije za održivi i ruralni razvoj gradova Siska, Petrinje i Hrvatske Kostajnice i općina Majur i Topusko, 2025)
Cultural heritage is an important resource for the development of local communities and provides significant economic, social and cultural benefits. The town of Sisak is an exceptional example of the importance of heritage conservation in strengthening community identity and promoting economic development. This paper analyses the challenges and opportunities in heritage conservation, focusing on investment, sustainability, the tourism offer, citizen engagement, and the potential of cultural tourism. Given the city’s rich history, one of the main objectives of the research was to develop strategies to improve heritage management systems. Sisak faces numerous obstacles, including limited financial resources, a lack of specialised staff, low awareness of the importance of cultural heritage, as well as the risk of earthquakes and inadequate infrastructure. It emphasises the need for investment in restoration, education and modern technologies such as digitisation and innovative methods of heritage interpretation to preserve it and make it more accessible. An approach that involves collaboration between local authorities, professionals and the community with the implementation of sustainable, authentic solutions is also crucial. Achieving this goal requires greater public awareness and continued financial and social investment to ensure the long-term protection and revitalisation of cultural heritage for future generations.